Using meristematic clumps as explants for long term conservation. - Wilms, Hannes; Fanega Sleziak, Natalia; Panis, Bart (2025)
Breeding programmes but also agriculture in general depend on the availability of the widest possible genetic diversity within of a species. The conservation of genetic resources is thus extremely important Whilst for many plant species multiple conservation methods have been developed, for some species with recalcitrant seeds such as the coconut palm (Cocos nucifera) the tools are limited. However, with the recent development of a new type of explant, coconut meristematic clumps, resulting from a novel shoot micropropagation method, this type of explant could be used for the long term conservation via cryopreservation. Meristematic clumps contain multiple meristems per explants which increases the chance for survival after cryopreservation since each meristems on the explant has the potential to grow. We opted for droplet vitrification and optimized the protocol by varying preculture time and composition, PVS2 treatment time, and explant size. After cryopreservation the explants were checked if they were still able to proliferate. In the current protocol around 50 % of explants survived liquid nitrogen exposure. However, subsequent browning during growth caused a 30% drop, resulting in 22% or less of explants that formed new meristems after cryopreservation. The material that survived was able to proliferate and regenerate into rooted plants, showing the potential of this explant for long term conservation purposes.